A Study On Difficulties In Doing Part 3 Of The End-Of Course Oral Test Faced By Third-Year Students Of Faculty Of English-University Of Foreign Language Studies-The University Of Danang (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
As English students, improving their speaking performance to meet the standards of their English language program and the end-of-course oral test is crucial. This study aims to identify the challenges faced by third-year students at FE-UFLD-UD in doing part 3 of the C1.4 end-of-course oral test, the factors behind these difficulties, and suggested solutions. 99 students who learned the C1.4 Speaking subject and took the C1.4 oral test were surveyed to gather the data. The study employed questionnaire to collect the data, Microsoft Office Excel and SPSS Software version 28 to analyze the collected information, and quantitative methods to investigate the difficulties and underlying causes. The key findings suggest that students struggle with affective, cognitive, and linguistic elements, and the reasons for these challenges. Possible solutions are also recommended based on the analysis of these causes. Importantly, the research encourages students who are struggling with part 3 in the C1.4 subject and preparing for the VSTEP to examine the difficulties that they meet and apply suggestions in their study habits to handle their difficulties. Moreover, teachers can take the findings as a reference to help students to improve their speaking skill.